SIMULATION KIT DISCHARGE LAMPS - THROTTLE IN MATLAB - and (Municipal economy of cities. Series: «Economy science», 2013)
The behavior of electrical parameters of the high pressure discharge lamp was investigated by computer simulation means. Results comparing with real measurements data confirm the used time-dependent processes model adequacy.